Fecal carriage of vancomycin-resistant enterococci in hospitalized patients and those living in the community in The Netherlands. - Endtz, H P (1997)
In order to determine the prevalence of vancomycin-resistant enterococci (VRE) in The Netherlands, 624 hospitalized patients from intensive care units or hemato-oncology wards in nine hospitals and 200 patients living in the community were screened for VRE colonization. Enterococci were found in 49% of the hospitalized patients and in 80% of the patients living in the community. Of these strains, 43 and 32%, respectively, were Enterococcus faecium. VRE were isolated from 12 of 624 (2%) and 4 of 200 (2%) hospitalized patients and patients living in the community, respectively. PCR analysis of these 16 strains and 11 additional clinical VRE isolates from one of the participating hospitals revealed 24 vanA gene-containing, 1 vanB gene-containing, and 2 vanC1 gene-containing strains. All strains were cross-resistant to avoparcin but were sensitive to the novel glycopeptide antibiotic LY333328. Genotyping of the strains by arbitrarily primed PCR and pulsed-field gel electrophoresis revealed a high degree of genetic heterogeneity. This underscores a lack of hospital-driven endemicity of VRE clones. It is suggested that the VRE in hospitalized patients have originated from unknown sources in the community.